FILSAFATA BAHASA: TIDAK TUTUR DALAM NOVEL “TOKO TUKAR TAMBAH NASIB” KARYA LIA SEPLIA (KAJIAN PRAGMATIK) - Junifer Siregar; Imam Baehaqie; Tommi Yuniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is an analysis of speech acts in the novel "Toko Tukar Tambah Nasib" by Lia Seplia using pragmatic studies to describe the meaning of the utterances used by the characters in the novel. The objectives of this study are (1) To describe locutionary speech acts in the novel "Toko Tukar Tambah Nasib" by Lia Seplia, (2) To describe illocutionary speech acts in the novel "Toko Tukar Tambah Nasib" by Lia Seplia and (3) To describe perlocutionary speech acts in the novel "Toko Tukar Tambah Nasib" by Lia Seplia. This analysis uses a qualitative approach and descriptive research methods. The data analysis techniques used in this study are observation techniques, library techniques, reading techniques, and note-taking techniques. Data analysis is carried out by means of data reduction, data presentation, and drawing conclusions/data verification. Based on the results of the study, it can be concluded that there are locutionary, illocutionary, and perlocutionary speech acts in the dialogue of the novel "Toko Tukar Tambah Nasib" by Lia Seplia. The locutionary speech acts in Lia Seplia's novel "Toko Tukar Tambah Nasib" (The Exchange Shop for Fate) consist of declarative, interrogative, and imperative locutions. The illocutionary speech acts in Lia Seplia's novel "Toko Tukar Tambah Nasib" consist of assertive, directive, commissive, expressive, and declarative speech acts. Perlocutionary speech acts are also present in Khrisna Pabichara's novel Natisha.